2007
DOI: 10.1002/eji.200636216
|View full text |Cite
|
Sign up to set email alerts
|

WC1+ γδ T cell memory population is induced by killed bacterial vaccine

Abstract: Limited studies have addressed the ability of cd T cells to become memory populations. We previously demonstrated that WC1.1 + cd T cells from ruminants vaccinated with killed Leptospira borgpetersenii proliferate and produce IFN-c in recall responses. Here we show that this response is dependent upon antigen-responsive CD4 T cells, at least across transwell membranes; this requirement cannot be replaced by IL-2. The response was also dependent upon in vivo priming, since cd T cells from leptospira vaccine-nai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 59 publications
6
41
0
1
Order By: Relevance
“…Though in our study this difference was not statistically significant, the data are similar to a study by Blumerman et al suggesting that memory WC1þ cells can be induced by killed bacterin. 2 A lack of antigenic specificity in naive gd T cells of cattle is consistent with previous reports. gd T cells are nonmajor histocompatibility restricted and thus directly respond to pathogen-associated molecular patterns.…”
Section: Discussionsupporting
confidence: 92%
“…Though in our study this difference was not statistically significant, the data are similar to a study by Blumerman et al suggesting that memory WC1þ cells can be induced by killed bacterin. 2 A lack of antigenic specificity in naive gd T cells of cattle is consistent with previous reports. gd T cells are nonmajor histocompatibility restricted and thus directly respond to pathogen-associated molecular patterns.…”
Section: Discussionsupporting
confidence: 92%
“…2) Lymphocyte proliferation in response to antigen. Lymphocytes were stimulated ex vivo with antigen prepared from highpassage L. borgpetersenii serovar Hardjo strain RZ33, providing uniformity with previous studies (3,4,9,18,19) and consistency within this experiment; RZ33 was used to prepare the Mono2 reference vaccine in this study and previous studies. PBMCs obtained from Mono1-vaccinated animals mounted a significantly higher proliferation response after exposure to antigen than either Mono2-vaccinated or control animals (Fig.…”
Section: Methodsmentioning
confidence: 91%
“…Others have reported that it has been difficult to generate Agspecific gd T cells following vaccination (42). Reports of gd T cell memory induction in the bovine (13,43) may indicate that, in this species, specific Ag-dependent stimulation of gd T cells may exist. It cannot be ruled out that gd T cell responses at such an early stage as reported in this study result from nonspecific stimulation by endogenously derived ligands.…”
Section: Discussionmentioning
confidence: 99%